Control of a Three-Input DC-DC Converter Suitable for DC Motors - Amin Alizadeh Asl; Seyed Hossein Hosseini; Naser Vosoughi Kurdkandi; Ramin Alizadeh Asl (International Transactions on Electrical Energy Systems)
A new multivariable control technique is introduced in this paper. This method is applied to a three-input DC-DC converter. First, the dynamic model of the converter is obtained in the state space, and then, the transfer function is achieved from the state space model to design a controller. In the second step, the input-output sets must be paired using a relative gain array (RGA) matrix. In the third step, the system is decoupled in the steady state by a simple matrix. The PI controller tracks the reference inputs of the controller. If the designed controller has proper performance in the transfer function of the converter, it can be applied to a real system. This multivariable control method has suitable performance and simple implementation, which results in an inexpensive controller. The DC motor must work in a constant power region if the practical application is the aim. In this case, the torque can be directly controlled to regulate the speed of the DC motor without needing a gearbox, which promotes total efficiency. Real-time simulation and experimental results verify the effectiveness of the proposed system.